Dystopian cybernetic environment in Kurt Vonnegut’s Slaughterhouse-Five - Babaee, Ruzbeh; Wan Yahya, Wan Roselezam; Sivagurunathan, Shivani (Academy Publisher, 2014)
Cybernetics is particularly well-suited to cultural history since it resonated with an American cultural mood that included World War II anxieties and worries that communism indicated that human beings could degenerate into unthinking, perfectly intelligent machines. Kurt Vonnegut’s Slaughterhouse-Five (1969) illustrates people who become enslaved to a controlling system of cybernetics that carries out its power through time and war. In this study, I examine Slaughterhouse-Five in which the cybernetic system creates a dystopian society and reduces human beings into obedient robots. Vonnegut’s Slaughterhouse-Five demonstrates that cybernetics as a metaphor for control of the mind leaves no space for individuals to decide for their own lives. This analysis investigates the ways through which cybernetics manipulates human beings in Vonnegut’s Slaughterhouse-Five.